Stress Testing Spillover Risk in Mutual Funds - Capponi, Agostino; Glasserman, Paul; Weber, Marko Hans (Management Science, 2025)
We develop a framework to quantify the vulnerability of mutual funds to fire-sale spillover losses. We account for the first-mover incentive that results from the mismatch between the liquidity offered to redeeming investors and the liquidity of assets held by the funds. In our framework, the negative feedback loop between investors’ redemptions and price impact from asset sales leads to an aggregate change in funds’ net asset value, which is determined as a fixed point of a nonlinear mapping. We show that a higher concentration of first movers increases the aggregate vulnerability of the system as measured by the ratio between endogenous losses triggered by fund redemptions and exogenous losses caused by initial price shocks only. When calibrated to U.S. mutual funds, our model shows that, in stressed market scenarios, spillover losses are significantly amplified through a nonlinear response to initial shocks that results from the first-mover incentive. Higher spillover losses provide a stronger incentive to redeem early, further increasing fire-sale losses and the transmission of shocks through overlapping portfolio holdings. This paper was accepted by David Simchi-Levi, finance. Funding: The research of A. Capponi has been supported by the National Science Foundation–Civil Mechanical and Manufacturing Innovation) CAREER grant [Grant 1752326]. The research of M. H. Weber has been supported by the NUS Start-Up grant [Grant A-0004587-00-00] and the Singapore MOE Tier 1 grant [Grant A-8000966-00-00]. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.03443 .